Anthocyanin-Rich Fraction of Black Rice Bran Extract Protects against Amyloid β-Induced Oxidative Stress, Endoplasmic Reticulum Stress, and Neuronal Apoptosis in SK-N-SH Cells - Sivanan Sivasinprasasn; Jiraporn Tocharus; Sugunya Mahatheeranont; Sarun Nakrat; Chainarong Tocharus (MDPI AG, 2024)
Alzheimer's disease (AD) is the most common neurodegenerative disorder in the aging population. An accumulation of amyloid plaques and neurofibrillary tangles causes degeneration of neurons, leading to neuronal cell death. The anthocyanin-rich fraction of black rice (Oryza sativa L. variety "Luem Pua") bran (AFBRB), extracted using a solution of ethanol and water and fractionated using Amberlite XAD7HP column chromatography, contains a high anthocyanin content (585 mg of cyanidin-3-O-glucoside and 24 mg of peonidin-3-O-glucoside per gram of the rich extract), which has been found to reduce neurodegeneration. This study focused on the neuroprotective effects of AFBRB in Aβ25-35-induced toxicity in the human neuroblastoma cell line (SK-N-SH). SK-N-SH was exposed to Aβ25-35 (10 µM) to induce an AD cell model in vitro. Pretreatment with AFBRB (0.1, 1, or 10 µg/mL) or C3G (20 µM) was conducted for 2 h prior to the treatment with Aβ25-35 (10 µM) for an additional 24 h. The results indicate that AFBRB can protect against the cytotoxic effect of Aβ25-35 through attenuation of intracellular ROS production, downregulation of the expression of the proteins Bax, cytochrome c, cleaved caspase-9, and cleaved caspase-3, upregulation of the expression of Bcl-2 in the mitochondrial death pathway, and reduction in the expression of the three major markers of ER stress pathways in similar ways. Interestingly, we found that pretreatment with AFBRB significantly alleviated Aβ-induced oxidative stress, ER stress, and apoptosis in SK-N-SH cells. This suggests that AFBRB might be a potential therapeutic agent in preventing neurodegenerative diseases.